Laboratory assessment of the effects of straw mulch on soil compaction under static and dynamic loads - Wang, Xianliang; Bai, Mingyue; He, Jin; Zhang, Xiangcai; Liu, Kaihua; Liu, Lei; Gao, Shang; Hu, Hong; Ji, Jiangtao (International Journal of Agricultural and Biological Engineering, 2025)
While straw mulching has been recognized for mitigating compaction, the multifactorial effects of straw parameters (content, length, laying modes) under static versus dynamic loads remain poorly quantified. Straw mulching may alter the stress transfer in the soil when applying static or dynamic loads. This study systematically evaluated stress and energy dissipation mechanisms using laboratory simulations: a plate sinkage test and an adapted Proctor test. The results demonstrated that the straw content (0-20 Mg/hm2) dominantly governs dissipation efficiency, with maximum stress dissipation ratios of 45.6% (static load >200 kPa) and energy dissipation ratios of 38.64% (dynamic high-energy). Longer straw (0.20 m) and ordered laying modes enhanced stress dispersion only under low static loads, while dynamic loads exhibited weaker dissipation. The study reveals that the damping effect of straw is strongest under low stress static load, so it is necessary to reduce the compaction of agricultural machinery and optimize the allocation of straw, such as 15-20 Mg/hm2, to alleviate compaction in clay loam soils. These findings can provide actionable insights for designing straw-based soil conservation strategies and improving compaction prediction models in mechanized agriculture. Key words: adapted Proctor test; agricultural engineering; soil compaction; straw mulching; stress dissipationDOI: 10.25165/j.ijabe.20251802.9315Citation: Wang X L, Bai M Y, He J, Zhang X C, Liu K H, Liu L, et al. Laboratory assessment of the effects of straw mulch on soil compaction under static and dynamic loads. Int J Agric & Biol Eng, 2025; 18(2): 21–26.